Analysis of the Effectiveness of Interpersonal Communication Strategies of Shield Agents at BPJS Ketenagakerjaan Makassar Branch Office - Syafranti, Yuyun (IHSA Institute, 2024)
The aim of this research is to analyze the effectiveness of interpersonal strategies of shield agents, as well as to analyze whether or not the implementation of interpersonal strategies is effective using the AIDDA method, namely Attention (attention), Interest (interest), Desire (Desire), Decision (Decision) and Action (action or activity). ) in increasing the number of participants at BPJS Employment Makassar Branch office. Data were collected through observation and conducting interviews with informants, namely leaders, staff and participants of BPJS Employment Makassar Branch office. The data analysis technique uses descriptive analysis and uses data reduction, data display, and data description. The results of the research show that the interpersonal strategy carried out by agents using the AIDDA strategy has been effective, where the shield agent is able to attract attention and arouse participants' interest through an emotional approach and intensive socialization. Apart from that, it is also effective in arousing the desires of potential participants so that it influences decisions by taking action for participants according to the shield agent's expectations by becoming a participant in one of the programs offered by BPJS Employment Makassar Branch office